Formação e trabalho do professor-tutor no Teleduc: autonomia e/ou heteronomia - Cavagnari , Daniel Weigert (2010)
It is presented in this dissertation research about the formation and work of the teacher-tutor in virtual learning environment Teleduc. One has to analyze the formation and work of the teacher-tutor, understanding that we are faced with a private practice, autonomous or heteronomous professional practice by imposing restrictions and tools to guide practice. Discusses issues related to training of teacher-tutor, their autonomy and / or heteronomy before classes at a distance via the Internet and tools with pre-defined textual mediation. This work aims to contribute to studies on teaching and distance learning that expands public and private HEIs in Brazil, especially the past decade here. Resorted to interviews and questionnaires to collect data that enabled us to analyze the formation and work of the teacher-tutor and the case study for understanding the locus of research was sufficiently representative so we can make inferences. The text is organized into four chapters. The first chapter dealt with the historical conjuncture of the 1990s, when the context of productive restructuring and neoliberal adjustments to new information technologies make accent, once formal education and appears Teleduc. The second chapter describes the Teleduc. In the third chapter in the teacher-tutor AVA Teleduc and in the fourth chapter, training and work of the teacher-tutor for the unveiling of two problems that we place: the formation and work of the teacher-tutor is guided by autonomy? And, or, by heteronomy? The relevance of the study is by the need for understanding of teacher and tutor in virtual learning environments in distance education.